2018
DOI: 10.4186/ej.2018.22.4.147
|View full text |Cite
|
Sign up to set email alerts
|

New Approach for Identification of Suitable Vibration Attenuation Relationship for Underground Blasts

Abstract: For construction and mining activities, excavation is often performed with the help of blasting in hard or weathered rock or even hard soil. As a safety practice, the blasting operation is designed so that the nearby structures are not adversely affected. For this, blast vibration attenuation relationship for the ground media becomes necessary. In India, the relevant IS code specifies an attenuation relationship (Power expression) between the peak particle velocity, the charge weight and the distance of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…rough the above analysis, it can be found that those comparison factors like crack, flatness, and damage are all related to excavation quality, whose influences are limited to the vicinity of the explosive source. Nevertheless, in practice, residents in the neighborhood are more concerned about the adverse impacts of blast-induced vibrations because they can propagate over long distances [24][25][26][27]. Hence, it is vital to investigate the vibration characteristics induced by blasting operations with two control techniques.…”
Section: Introductionmentioning
confidence: 99%
“…rough the above analysis, it can be found that those comparison factors like crack, flatness, and damage are all related to excavation quality, whose influences are limited to the vicinity of the explosive source. Nevertheless, in practice, residents in the neighborhood are more concerned about the adverse impacts of blast-induced vibrations because they can propagate over long distances [24][25][26][27]. Hence, it is vital to investigate the vibration characteristics induced by blasting operations with two control techniques.…”
Section: Introductionmentioning
confidence: 99%
“…• It did not cover the uncertainties in model structure, which would include the expression form for the PPV. Methods to arrive at the best suited expression form for any site have been discussed in literature [7]. • The expression form for scaled distance (SD) was fixed, and uncertainty therein was not examined.…”
Section: Discussionmentioning
confidence: 99%
“…The trial blasting should be designed such that the area under consideration is represented well, with around 40 numbers of data sets, for development of the vibration attenuation relationship. First, the suitable equation form applicable for the site should be identified as elucidated in literature [7] from the trial blast data. Thereafter, employing the proposed methodology of re-sampling (each sample having, say, 30 data sets or more), the probability density functions should be established for the parameters of the chosen expression form.…”
Section: Implementation Of the Proposed Methodology For Practical Desmentioning
confidence: 99%
See 2 more Smart Citations